Compatibility of Constitutional and Supreme Court Decisionson Small Island Protection - Gustiyanti Tangahu; Fence M. Wantu; Supriyadi A. Arief (Nusantara: Journal of Law and Islamic Law, 2026)
This study examines the legal consistency between Constitutional Court Decision No. 35/PUU-XXI/2023 and Supreme Court Decision No. 57P/HUM2022 regarding small island protection in Indonesia. It focuses on the judicial review of the Coastal Area and Small Islands Management Law following a mining dispute on Wawonii Island. The research employs a normative legal method with statutory and casebased approaches. Findings indicate that the Constitutional Court affirms the prohibition of mining on small islands as conditional, rather than absolute, contingent upon technical, ecological, and socio-cultural impacts. Simultaneously, the Supreme Court categorizes such activities as abnormally dangerous, reinforcing environmental safeguards. This judicial synchronization establishes a robust regulatory framework that prioritizes sustainability, tightens environmental permitting instruments, and ensures legal certainty for stakeholders. These rulings strengthen the constitutional rights of coastal communities against exploitative activities, mandating that natural resource utilization must strictly adhere to rigorous ecological standards to prevent irreversible damage to vulnerable island ecosystems.